2013
DOI: 10.1590/s1516-35982013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Use of orthogonal functions in random regression models in describing genetic variance in Nellore cattle

Abstract: -A total of 204,912 records of birth weights up to 550 days of age, of 24,890 Nellore cattle, offspring of 375 sires and 16,917 dams from five herds in the state of Mato Grosso, Brazil, were used in order to describe the variability of the weight development by random regression models. The model evaluated as the most suitable used the covariance function of fourth order to describe the variability of the effects of additive genetic, animal permanent environmental and maternal effects of third order to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, Loaiza-Echeverri et al (2013) investigated Guzerat cattle and reported higher values for W450, ranging from 0·52 to 0·60. Slightly higher heritability estimates for W450 (0·56) were observed by Silva et al (2013) for Nellore. Guidolin et al (2012) reported heritability estimates ranging from 0·2 ± 0·07 to 0·7 ± 0·05 for Nellore in a genotype × environment interaction study.…”
Section: Discussionmentioning
confidence: 61%
“…However, Loaiza-Echeverri et al (2013) investigated Guzerat cattle and reported higher values for W450, ranging from 0·52 to 0·60. Slightly higher heritability estimates for W450 (0·56) were observed by Silva et al (2013) for Nellore. Guidolin et al (2012) reported heritability estimates ranging from 0·2 ± 0·07 to 0·7 ± 0·05 for Nellore in a genotype × environment interaction study.…”
Section: Discussionmentioning
confidence: 61%
“…High genetic correlations among bodyweight traits were observed by Vargas et al (2014), Neser et al (2012), andVan Niekerk andNeser (2006) for Brahman, Brangus, and Limousin breeds. Silva et al (2013b) estimated genetic correlations for Nellore cattle from birth to 550 days of age, which varied from 0.25 to 0.98. Selection of any of these traits would increase bodyweight gains at later ages.…”
Section: Resultsmentioning
confidence: 99%